MACROECONOMIC CONTRIBUTIONS OF SMALL AND MEDIUM ENTERPRISES TO ECONOMIC GROWTH IN NIGERIA (Journal of the Management Sciences, 2025)
This study examines the macroeconomic contributions of Small and Medium Enterprises (SMEs) to Nigeria’s economic growth from 1999 to 2023 using an Ordinary Least Squares (OLS) regression framework. The results show that SME activity has a positive and significant effect on Gross Domestic Product (GDP), with a 1% increase in SME activity raising GDP by about 0.07%. Government expenditure and employment growth also exert strong positive effects, underscoring the importance of public investment and job creation policies in stimulating growth. Conversely, corruption negatively affects GDP, highlighting the need for governance reforms. Access to finance, measured by commercial bank credit and lending rates to SMEs, significantly influences growth, emphasizing the role of financial accessibility in supporting enterprise development. The model explains 39% of GDP variation and is statistically significant. The study recommends that policymakers strengthen SME financing mechanisms, curb corruption, and channel more government spending toward enterprise development. Enhancing employment and credit policies will further amplify the macroeconomic benefits of SMEs, contributing to sustainable growth in Nigeria.
Keywords: Small and Medium Enterprises; GDP; Government Expenditure; Employment; Corruption; Credit.